Analisis Indeks Glikemik dan Beban Glikemik Minuman Sereal Berbasis Kedelai, Oat dan Madu Randu dengan Penambahan Bubuk Daun Kelor - Hilmy Mumtaz; Ibnu Malkan Bakhrul Ilmi; Avliya Quratul Marjan (Jurnal Ners, 2026)
Type 2 diabetes melitus is a chronic disease caused by insulin resistance. In 2023, the prevalence of type 2 DM in Indonesia among people aged ≥15 years continued to increase, reaching 11.7% among people of productive age. e implementation of a natural food-based diet with high fiber and low glycemic index is important in controlling blood glucose in people with type 2 diabetes. This study aims to describe the glycemic index and glycemic load values of test cereal drinks with added moringa leaves and compare them with commercial products. The study used a true experimental design with a crossover design on 10 subjects who met the inclusion and exclusion criteria. The treatment was given three times in the form of pure glucose, commercial cereal, and moringa leaf test cereal with a minimum washout period of three days. Blood glucose was collected at 0, 15, 30, 45, 60, 90, and 120 minutes, followed by the calculation of the glycemic index using IAUC method and glycemic load. The results showed that the moringa leaf test cereal had a GI value of 50.71% (low category), whilst the commercial cereal had a value of 61.06% (moderate category). The commercial cereal had a BG value of 11.60 (moderate category), whilst the test cereal had a value of 7.72 (low category). It was concluded that the moringa leaf test cereal effectively provided more stable postprandial blood glucose control due to its high fiber content and low glycemic index value.